Andrea B. Rugh: Within the Circle. Parents and Children in an Arab Vdlage. - Galal, Lise P. (Tidsskriftet Antropologi, 1998)
Andrea B. Rugh: Within the Circle. Parents and Children in an Arab Vdlage. Anmeldes af Lise P. Galal